2005
DOI: 10.1111/j.1475-097x.2005.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Maximal oxygen uptake at the same fat‐free mass is greater in men than women

Abstract: Maximal oxygen uptake (VO(2max)) is commonly divided by body mass or fat-free mass (body mass minus fat mass) in order to make it size independent so that comparisons among persons of different size can be made. However, numerous studies have shown that the ratio created is not size-independent. Analysis of covariance (ANCOVA) allows a dependent variable to be compared between groups at a common value of a covariate. The purpose of this study was to compare VO(2max) at the same fat-free mass (FFM) in 230 seden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Our participants were female physically active students, and their aerobic capacity may be considered higher because of the 10–15% difference between female and male untrained persons, as well as athletes, because of morphophysiological differences [26]. VO 2 max at the same fat-free mass is considerably (~30%) higher in sedentary men than in sedentary women [27]. Mild hypohydration exacerbates cardiovascular and thermoregulatory strain and tends to impair endurance performance, but greater aerobic fitness attenuates these physiological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Our participants were female physically active students, and their aerobic capacity may be considered higher because of the 10–15% difference between female and male untrained persons, as well as athletes, because of morphophysiological differences [26]. VO 2 max at the same fat-free mass is considerably (~30%) higher in sedentary men than in sedentary women [27]. Mild hypohydration exacerbates cardiovascular and thermoregulatory strain and tends to impair endurance performance, but greater aerobic fitness attenuates these physiological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Among the physiologic correlates of VO 2peak in healthy populations, fat free mass (FFM) is increasingly recognized as an important factor in both adults and children . FFM may influence aerobic capacity through augmentation of the skeletal muscle pump and venous return, and it has been suggested that FFM may account for observed sex differences in VO 2peak . Among children, the relationship between FFM and VO 2peak may be dependent on pubertal maturity, as both increase during adolescence .…”
Section: Introductionmentioning
confidence: 99%
“…VO 2 and VO 2 max values are commonly reported per body mass, but less commonly per lean body mass, fat free mass, or skeletal muscle mass (SMM), in order to offset sex differences based on varying body composition between the sexes ( Lewis et al, 1986 ; Price et al, 2022 ). Nevertheless, men may still yield higher VO 2 max values of up to 27% based on fat free mass compared to women ( Davis et al, 2006 ). Since VO 2 resembles energy expenditure of about 20 kJ/l oxygen ( Brooks, 2012 ) and is connected to MPO through the factor of exercise efficiency ( Böning et al, 2017 ), evaluating MPO not only in absolute terms or per body mass (BM) ( Hettinger et al, 1961 ), but also per SMM would be of interest.…”
Section: Introductionmentioning
confidence: 99%